Service Quality Assessment of Janakeeya Hotels : Social Enterprise Performance Analysis - M., Preenu Antony; S., Jithendran (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : The present study focused on examining customer perceptions of service quality at Janakeeya Hotels, a community–driven initiative of Kudumbashree aimed at providing affordable meals to economically vulnerable people. Design/Methodology/Approach : The study employed established service quality models––SERVQUAL, DINESERV, and CFFRSERV––to assess customer satisfaction across six dimensions: tangibility, reliability, food quality, responsiveness, assurance, and empathy. A structured questionnaire was administered to customers visiting Janakeeya Hotels across Kerala, with data collected from both regular and irregular customers. The analysis examined service quality perceptions across demographic variables. Findings : The findings revealed the importance of customer retention strategies and consistent service delivery in building positive perceptions and satisfaction. Practical Implications : Management should prioritize strategies to convert irregular customers into regular customers through consistent service quality. The findings emphasized the importance of maintaining high service standards across all dimensions to ensure long-term sustainability and social impact of the initiative. Originality : This study filled a critical gap by comparing regular versus irregular customers’ perceptions and analyzing demographic variations in service quality assessments for social entrepreneurship ventures focused on economically vulnerable populations.